Two monopoles of one type and one of another - HOUGHTON, CONOR JAMES (Institute of Physics, 1999)
The metric on the moduli space of charge (2,1) SU(3) Bogomolny- Prasad-Sommerfield monopoles is calculated and investigated. The hyperkahler quotient construction is used to provide an alternative derivation of the metric. Various properties of the metric are derived using the hyperkahler quotient construction and the correspondence between BPS monopoles and rational maps. Several interesting limits of the metric are also considered.
PUBLISHED
Keywords: Solitons Monopoles and Instantons, Integrable Field Theories.